(untitled) (Global Journal of Medical Research, 2021)
Introduction-According to the Centers for Disease Control and Prevention (CDC) in March 2021, the United States (U.S.) had over 30 million cases and 547,296 deaths. A lot of change has occurred that is continuing to scar the emotions, affect, behavior, and mental psyche of everyone. Socialization and peer interactions are an important developmental milestone in school-age children (APA, 2021). Internationally, approximately 90% or 1-5 billion enrolled school-age children have been out of education due to the pandemic closures or restrictions (Lee). Covid-19 has led to adverse outcomes in communities with destruction, aggression or anxiety in people, deaths, grief, anxiety, depression, fear, and possible future long-term impacts that are still yet to be fully determined. A study by Brooks et al., found loss or limitations experienced by children are contributing to increased stress, fear, sedentary lifestyles, increasing obesity, depression, aggressive behaviors, substance abuse, suicides, boredom, cyberbullying, abuse, neglect, and family financial crisis.